A study on factors that affect the successful of succession planning at institute of higher education in Batu Pahat / Rashidah Ismail and Nor Albaniah Ahmad Zakaria - Ismail, Rashidah; Ahmad Zakaria, Nor Albaniah (2014)
Succession planning is used as an essential and strategic tool for the organizations to attract, develop, and retain talent in the workforce. As a comprehensive definition, succession planning can be defined as an attempt to have a plan for the right number and quality of key position employees, including managers to cover retirements, promotions, serious illnesses, death or any new job, which may be created in the future of the organization’s plans. When there is a supportive and committed group that implement this tool, the organization must be ready towards any possibilities as they have their own future best talent. The past researcher shows that there are some factors or conditions that will affect the implementation or the succession planning process. The present research has study on four factors that may affect the successful of succession planning which are commitment, skills, knowledge, and motivation. This study has been conducted within Universiti Tun Hussein Onn Malaysia and Kolej Poly-Tech Mara Batu Pahat which it was involved by 180 respondents of academic and non- academic staff of both institutes. Results from the present study showed that the most affect the successful of succession planning is commitment. Recommendations for organization and future research also have been discussed.